Determining The Effectiveness of Going Concern Audit Opinion by ISA 570 - Ni Nyoman Alit Triani; Made Dudy Satyawan; Merlyana Dwinda Yanthi (Asian Journal of Accounting Research, 2017)
The research aims to address the Going Concern Audit Opinion published by the auditor with an ISA 570 basis. The application of ISA 570 will help to facilitate the auditor in publishing the Going Concern Audit Opinion. The Going Concern Audit Opinion is the opinion which is released by the auditor to assure whether the company is enabled to maintain its viability. The difference between SA 341 and ISA 570 will to contribute effective impact to the management for elucidating the management plan undertaken to overcome any difficulty they may encounter. The ISA 570 will represent that the auditor intensely guides the management in plan or strategy development for upgrading the finance and non-finance performance. The research approach is the Non-Positivistic approach from an Interpretive Perspective. The researcher obtains the source and type of data from key persons consisting of all auditors working in Public Accountant Firms (PAF) in Surabaya. The data collecting technique uses observation, interview and documentation. The result of the research shows the ISA 570 application gives the facility for the auditors in publishing a Going Concern Audit Opinion. In the audit execution, the auditor will accentuate the strategic plan for resolving the problems with which the company deals.